A new species of Leposternon Wagler, 1824 (Squamata, Amphisbaenia) from northeastern Argentina - Ribeiro, Siria; Santos-Jr, Alfredo P.; Zaher, Hussam (Zootaxa, 2015)
A new species of Leposternon is described from the Humid Chaco biome in Argentina. The species is known only from its type locality, at El Bagual Ecological Reserve, a conservation unit located in the province of Formosa. The new species can be distinguished from all its congeners by the presence of rostral processes in the maxillae and nasals that contact each other on the facial portion of the skull. Additionally, we present a key for the species of Leposternon.